2000
DOI: 10.1034/j.1600-0676.2000.020001051.x
|View full text |Cite
|
Sign up to set email alerts
|

Central and systemic haemodynamic effects of terlipressin in portal hypertensive patients

Abstract: Terlipressin significantly attenuates the hyperdynamic circulation in portal hypertensive patients without a further contraction of the central and arterial blood volume. The systemic haemodynamic response to terlipressin is moreover associated with the decrease in portal pressure. Terlipressin may therefore have potentially beneficial effects on the hyperdynamic circulation in cirrhosis in addition to its effects on portal pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(108 citation statements)
references
References 0 publications
4
101
0
3
Order By: Relevance
“…Terlipressin activates the V1 receptors, which are predominantly located in the vasculature in the splanchnic region, causes vasoconstriction, 28 and thereby reduces the splanchnic arterial vasodilatation and portal pressure and ameliorates the hyperdynamic circulation. 14,29 This improves the effective circulatory volume and renal perfusion pressure. 23,29 In this study, we showed that these improvements in hemodynamics are associated with an increase in GFR and a deactivation of vasoconstrictors and sodium-conserving hormones (that is, norepinephrine and renin).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terlipressin activates the V1 receptors, which are predominantly located in the vasculature in the splanchnic region, causes vasoconstriction, 28 and thereby reduces the splanchnic arterial vasodilatation and portal pressure and ameliorates the hyperdynamic circulation. 14,29 This improves the effective circulatory volume and renal perfusion pressure. 23,29 In this study, we showed that these improvements in hemodynamics are associated with an increase in GFR and a deactivation of vasoconstrictors and sodium-conserving hormones (that is, norepinephrine and renin).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms behind the effect of terlipressin in HRS have not been thoroughly investigated. Terlipressin seems to revert the systemic vasodilatation and increase blood pressure 14 and thereby improve renal perfusion pressure and renal function. As HRS is most often preceded by the development of ascites, vasoconstrictors may also have a beneficial effect in decompensated cirrhosis without severe renal impairment and thereby represent a novel future treatment for ascites.…”
mentioning
confidence: 99%
“…In the latter patients, the acute administration of terlipressin alone (1-2 mg, intravenous bolus) evokes systemic vasoconstrictor and vasopressor effects associated with bradycardia and a reduction in cardiac output. 30,31 Finally, 2-day terlipressin administration is known to induce an arterial vasopressor effect associated with significant decreases in plasma renin concentrations and significant increases in GFR. 32 The effects of 1 to 2 weeks' administration of ornipressin or terlipressin alone on systemic hemodynamics are unknown.…”
Section: The Use Of Vasoconstrictors For Type 1 Hrsmentioning
confidence: 99%
“…However, no evidence of arterial underfilling was found in an acute hemodynamic study on the effects of the administration of 2 mg terlipressin in patients with cirrhosis. 31 Clearly, hemodynamic studies after 1 to 2 weeks' terlipressin administration are needed.…”
Section: The Use Of Vasoconstrictors For Type 1 Hrsmentioning
confidence: 99%
“…1 It is a biologically inactive substance that gains its long half-life of 2-10 hours by being enzymatically cleaved into the biologically active lysine-vasopressin. 13 It has been shown to cause direct vasoconstriction of the systemic arteriolar and splanchnic vasculature. It affects the V 1 vasopressin receptors of systemic vasculature more strongly than the V 2 vasopressin receptors of the kidneys.…”
Section: Hemodynamic Effects Of Terlipressin On Portal Hypertensionmentioning
confidence: 99%